2001
DOI: 10.1046/j.1365-3083.2001.00958.x
|View full text |Cite
|
Sign up to set email alerts
|

IL‐4‐Dependent Effector Phase in Autoimmune Exocrinopathy as Defined by the NOD.IL‐4‐Gene Knockout Mouse Model of Sjögren's Syndrome

Abstract: NOD mice manifest many features of autoimmune exocrinopathy (Sjögren's syndrome), a disease generally characterized by a chronic, progressive immunological attack against the exocrine tissues of the salivary and lacrimal glands. Previous studies using the NOD congenic partner strain, NOD.Igμnull, defined an important role for B lymphocytes in the development of xerostomia, implicating autoantibodies reactive with the acetylcholine muscarinic receptor (M3R) as the possible effector mechanism. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 30 publications
3
83
0
Order By: Relevance
“…In previous studies by our group, elimination of IFN␥ in SS-susceptible mice ameliorated all pathologic and clinical signs of disease, while elimination of IL-4 prevented loss of secretory function (40,43). These observations indicate an essential role for both Th1 celland Th2 cell-associated cytokines.…”
Section: Discussionsupporting
confidence: 58%
“…In previous studies by our group, elimination of IFN␥ in SS-susceptible mice ameliorated all pathologic and clinical signs of disease, while elimination of IL-4 prevented loss of secretory function (40,43). These observations indicate an essential role for both Th1 celland Th2 cell-associated cytokines.…”
Section: Discussionsupporting
confidence: 58%
“…In phase 3, secretory dysfunction of the salivary and lacrimal glands occurs, most likely the result of production of Abs reactive with the muscarinic acetylcholine receptors (6,29), marked by significant loss of secreted proteins. An aberration within any one of these three phases, e.g., disruption of either the IFN-␥ (20) or IL4 gene (19,22), interrupts subsequent onset of clinical SjS-like disease.…”
Section: Pathophysiological Characteristics Of Sjsmentioning
confidence: 99%
“…Ϫ/Ϫ mice indicated that IgG1 isotype-specific anti-M3R autoantibodies were the more important autoantibody, acting as potential effectors of secretory dysfunction observed in submandibular and lacrimal glands (19,22). To determine the presence of anti-M3R Abs, aliquots of sera pooled from appropriate groups were incubated with mouse M3R-transfected Flp-In CHO cells, tagged using FITCconjugated anti-isotype-specific secondary Abs, and subsequently analyzed by flow cytometry (26).…”
Section: Aec1aec2c3mentioning
confidence: 99%
“…Interestingly, both NOD.IL4 Ϫ/Ϫ and NOD.B10-H2 b .IL4 Ϫ/Ϫ mice failed to produce M3R autoantibodies of the IgG1 isotype (19,20). IL-4 is a pleiotropic cytokine involved in cell proliferation, activation, and differentiation (21).…”
mentioning
confidence: 99%